Relation between distal airspace size, bronchiolar attachments, and lung function. Issue 10 (October 1993) - Lamb, D; McLean, A; Gillooly, M; Warren, P M; Gould, G A; MacNee, W
Abstract : BACKGROUND--Smoking related fixed airway obstruction may be due to airway scarring and narrowing or decreased support due to loss of adjacent alveolar walls. In this study of resected specimens, preoperative pulmonary function was compared with results of a morphometric study of lung structure. METHODS--Morphometric measurements were made on 42 inflation fixed lung specimens as follows: airspace wall surface area per unit volume (AWUV) was measured on at least 25 l mm2 histological fields from each specimen, expressed as a mean, and the mean of the lowest five measurements for each case (LF5). Minimum diameter, maximum diameter, diameter ratio (ellipticality), lumen area, and lumen circumference were measured on at least 16 non-respiratory bronchioles from each lung. Peribronchiolar alveolar support was measured as mean interalveolar attachment distance (IAAD). Measurements of pulmonary function included forced expiratory volume in one second (FEV1) (absolute and % predicted values; n = 42), slope of phase III (single breath nitrogen test; n = 28), closing volume (expressed as a percentage of vital capacity (CV/VC%); n = 28). RESULTS--Bronchiolar size was not independently related to the tests of lung function used. Percentage predicted FEV1 was related to mean IAAD, ellipticality, and mean AWUV. CV/VC% showed significant relation with ellipticality, mean AWUV, and LF5 AWUV. Slope of phase III increased with increasing IAAD. Significant correlations were found between ellipticality and AWUV (mean and LF5), and between ellipticality and IAAD. Both IAAD and ellipticality were significantly increased in patients with abnormally low FEV1. CONCLUSION--Destruction of airspace walls, particularly those attached to the peripheral bronchioles, is more influential in determining airflow limitation than bronchiolar size.